Земля: полная энциклопедия / Е. Г. Ананьева, С. С. Миронова ; худож. Н. Краснова, Н. Парамыгин, О. Левченко - Ананьева Елена Германовна (Эксмо, 2009)
Экземпляры: СФ-18 (20100914) / Инвентарный номер: 39071 / Цена: 493.57 / Сис.шифр: 26.2 / Авт.знак: А 64 / ББК: 26.2